Algorithms for the treatment of patients with chronic cerebral ischemia of stages I and II with use of Picamilon: results of an open clinical comparative study - Andrei B. Danilov; Natalia N. Shindryaeva; Irina V. Borodulina; Timothy D. Lunegov (Consilium Medicum)
Aim. To study the efficacy and safety of Picamilon in patients with stages I and II of chronic cerebral ischemia (CCI).